Influência da superfície dentinária bovina na resistência de união de sistemas adesivos - Lara, Rafael Alves de [UNESP] (2014)
The aim of this study was to evaluate the influence of bovine dentin surface on the bond strength (BS) of two adhesive systems. In two groups (n = 5) buccal enamel of bovine incisors was removed by exposing the middle dentin. In the other two groups bovine teeth were ground from the lingual surface exposing the buccal wall of the pulp chamber. The teeth were ground flat and polished on sequentially with # 120 to 600 sandpapers in order to standardize the smear layer. The adhesives were Single Bond 2 (3M - ESPE) (SB2) and ClearFill (Kuraray) (CF). A block of composite resin (TPH 3, Dentsply) was constructed on the adhesive treated surface. After storage for 24 hours at 37 °C, each set was sectioned in X and Y (ISOMET 1000, Buehler) axes to obtain i-shaped specimens, with 1 mm² cross sectional area. The BS was obtained by mechanical microtensile testing in a universal testing (EMIC DL - 1000) using the Geraldeli's device at cross head speed of 0.5 mm/min. The fractures were examined under a stereomicroscope and classified into two categories: Type I - adhesive fracture, type II - mixed fracture. Data of bond strength (MPa) were submitted to 2-way ANOVA and Tukey's test for comparison between groups, both with α = 0.05. With the average values for the groups tested as follows: G1 (normal/Conventional) = 43,9 ± 4,8 MPa, G2 (invert/conventional) = 29,2 ± 5,4 MPa; G3 (normal/self-etching) = 13,9 ± 2,1 MPa and G4 (invert/self-etching) = 12,7 ± 3,4 MPa with significance for the direction of the dentin for adhesive systems as well as for the interaction of factors. Limited by the methodology of the study it can be concluded that the direction of bonding influences on the bond strength primarily in self-etching adhesives